Pembakuan Rasm Riwayat Abu ‘Amr Ad-Dani dalam Mushaf Standar Indonesia - Fais, Nor Lutfi; Khasanah, Nurul; Al Muafa, Kun Khoiro Umam (Lajnah Pentashihan Mushaf Al-Qur'an, 2022)
This study intends to study the factors that led to the standardization of mushaf rasm of the Indonesian Usmani Standard Qur’an to the narrations of Abu ‘Amr ‘Usman ad-Dani. This standard is available in a brief description (at-ta'rif bi al-mushaf ) on the back page of the mushaf of the Qur’an published by the Ministry of Religion for 2020 and 2021 editions. This is the peak of the recognition after the 1974-1983 Ulama Working Conference which had standardized the use of this ad-Dani riwayah rasm for the Indonesian standard manuscripts. This literature review research wants to answer the reasons behind the choice of Dani’s rasm usmani history and to conduct tarjih (triangulation) on it rather than the history of Abu Dawud Sulaiman ibn Najah which is widely used by mushafs from the Middle East. The result of this study found that the affiliation of history to rasm usmani ad-Dani was caused by several factors such as the similarity of the rules of rasm by ad-Dani with conventional Arabic writing, the familiarity of reading tradition of Indonesian people towards mushafs with rasm imla’i, the low level of public knowledge of the use of rasm in writing the Qur’an, and the use of al-Itqan by as-Suyuti as a reference